The Role of Indonesian Language Teachers in Era 5.0: Technology-based Learning Innovations and Artificial Intelligence - Hidayatul Hasani (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This research aims to identify the role of Indonesian language teachers in the 5.0 era, as well as explain technology-based learning innovations and artificial intelligence (AI) that can be applied in teaching Indonesian language. In addition, this research also aims to provide an overview of strategies that can be used to overcome the challenges that arise in technology-based learning. The method used in this research is a literature study, by analysing various sources related to the application of technology and AI in Indonesian language learning in the digital era. The results show that Indonesian language teachers in the 5.0 era act as facilitators who integrate technology and AI in the learning process. Learning innovations such as automated grammar apps, chatbots, and student data analysis using AI can improve the effectiveness of Indonesian language teaching. However, technical challenges such as limited access to technology and non-technical challenges such as students' adaptation to technology-based learning need to be addressed. To that end, proposed solutions include collaboration between the government, educational institutions, and communities as well as strengthening digital literacy for students and teachers. Personalised and interactive technology-based learning is key in facing these challenges and ensuring the success of Indonesian language learning in the 5.0 era